2020
DOI: 10.1007/s00345-020-03356-z
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive complication index (CCI): proposal of a new reporting standard for complications in major urological surgery

Abstract: Purpose The comprehensive complication index (CCI) is a new tool for reporting the cumulative burden of postoperative complications on a continuous scale. This study validates the CCI for urological surgery and its benefits over the Clavien-Dindo-Classification (Clavien). Material and methods Data from a prospectively maintained data base of all consecutive patients at a university care-center was analyzed. Complications after radical cystectomy (RC), radical prostatectomy (RP), and partial nephrectomy (PN) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The CCI was calculated based on CDC with the freely available calculator at www.assesssurgery.com. In contrast to the CDC, the CCI provides in general a continuous scale from 0 (no complication) to 100 (death of the patient), allowing an easier comparison between treatment groups [16,17,22,23]. However, due to the low range and small values of the observed CCI in our sample, we additionally categorized the CCI into (a) CCI = 0 meaning no complications; (b) CCI >0 and <26.2 (which marks a IIIa complication on the CDC) reflecting minor complications; and (c) ≥26.2 as a measure of major complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCI was calculated based on CDC with the freely available calculator at www.assesssurgery.com. In contrast to the CDC, the CCI provides in general a continuous scale from 0 (no complication) to 100 (death of the patient), allowing an easier comparison between treatment groups [16,17,22,23]. However, due to the low range and small values of the observed CCI in our sample, we additionally categorized the CCI into (a) CCI = 0 meaning no complications; (b) CCI >0 and <26.2 (which marks a IIIa complication on the CDC) reflecting minor complications; and (c) ≥26.2 as a measure of major complications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Comprehensive Complication Index (CCI), which is based on the CDC but summarizes the cumulative burden of complications on a continuous scale from zero (no complication) to 100 (death), was tested as an appropriate end point to compare complications between both groups [16, 17]. Furthermore, the CCI was validated of major uro-oncological procedures such as PN, radical prostatectomy, and radical cystectomy [18].…”
Section: Introductionmentioning
confidence: 99%
“…CRS and HIPEC surgeries can significantly influence the overall disease-free survival in selected patients suffering from peritoneal surface malignancies (PSM) [ 6 ]. The most common causes for post HIPEC complications and readmissions include failure to thrive, infection, and ileus and bowel obstruction (Table 1 ) [ 7 , 8 ]. Our patient presented three years after his initial surgery decreasing the likelihood of these complications being the cause of his symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The Comprehensive Complication Index (CCI) 39 which was previously validated for major urological surgery and that is based on the Clavien Dindo classification will be used. 40 41 Since several studies showed lack of standardisation when reporting intraoperative and postoperative complications, 42 43 the latter will be assessed according to the EAU guidelines on reporting and grading complications after urologic surgical procedures.…”
Section: Methods and Analysismentioning
confidence: 99%